Physicians’ Medicinal Practices Adopted by Consumers & Medical Representatives - Factor Analysis - A. , Suresh Kumar; S. , Fabiyola Kavitha (International Journal of Psychosocial Rehabilitation, 2020)
An Indian Pharmaceutical Industry today is in the front rank of India’s science-based industries with wide ranging capabilities in the complex field of drug manufacture and technology. A highly organized sector, the Indian Pharmaceutical industry is estimated to be worth 4.5 billion, growing at about 8 to 9 percent annually. It ranks very high in the third world, in terms of technology, quality and range of medicines manufactured. From simple headache pills to sophisticated antibiotics and complex cardiac compounds, almost every type of medicine is now made indigenously.